Chances for Socially Sustainable Development in Guam as One of the Remaining Colonies - Nennstiel, Ulrike (European Journal of Sustainable Development, 2019)
While colonialism might have some positive effects on the economy in the short term, it definitely impedes socially and ecologically sustainable development. Based on expert interviews with representatives of various NGOs and university professors, the paper discusses the chances of socially sustainable development in Guam as one of the colonies left today. The results show that colonialism today is having no less negative impacts on sustainable development than in the past. The economic conditions may have improved for some people, but socioeconomic inequalities have hardly decreased. Within former communities as well as among newcomers, many families are disrupted, addiction and suicide have spread particularly among youths and the number of homeless people is increasing. It becomes very clear that colonial and postcolonial conditions have to be overcome as a precondition to sustainable development. Keywords: Colonialism, social and ecological sustainability, Pacific islands